The intention to use e-money transaction in Indonesia: Conceptual framework - Khatimah, Husnil; Halim, Fairol (2013)
The issue of behavioral intention to use electronic transaction is backed up with rapid change in all types of traditional transactions. Electronic money (e-money) exists as new technology for electronic transaction.However, it is still ineffective in Indonesia where majority of the consumer prefer to use manual transaction business in the Bank and using cash notes.This is a potential for crime when they bring a lot of money to the Bank and thus have impact the Indonesian economy.E-money is a stored value or prepaid products that had recorded the funds or value and it can be done in online and offline transaction. Behavioral intention is a process in any type of actual behavior with giving the expression in making decision to the adoption of behavioral intention. This study attempts to explain consumers’ intentions to participate in the e-money transaction through the model that integrates the TPB (Theory of Planned Behavior) and the TAM (Technology Acceptance Model). Five major variables or focus of the concept and practice of e-money transaction have been studied in this article.The conceptual framework of e-money transactions were reviewed to understand behavioral intention of consumers from perceived usefulness, perceived ease of use, perceived risks, security and encouraging a learning system transaction. The proposed framework and hypotheses were presented in this article. Quantitative method will be utilized as sources of data collection.A total of one thousand and five hundred respondents will be selected using purpose sampling method in Medan, Indonesia. Descriptive analysis and Multiple Regression analysis will be conducted to analyze the data. The article ended with suggestion for future studies.